A Gonococcal Vaccine Has the Potential to Rapidly Reduce the Incidence of Neisseria gonorrhoeae Infection Among Urban Men Who Have Sex With Men. (11th December 2021) - Hui, Ben B; Padeniya, Thilini N; Rebuli, Nic; Gray, Richard T; Wood, James G; Donovan, Basil; Duan, Qibin; Guy, Rebecca; Hocking, Jane S; Lahra, Monica M; Lewis, David A; Whiley, David M; et al.
Abstract: Background: A gonococcal vaccine is urgently needed due to increasing gonorrhea incidence and emerging multidrug-resistant gonococcal strains worldwide. Men who have sex with men (MSM) have among the highest incidences of gonorrhea and may be a key target population for vaccination when available. Methods: An individual-based, anatomical site-specific mathematical model was used to simulate Neisseria gonorrhoeae transmission in a population of 10 000 MSM. The impact of vaccination on gonorrhea prevalence was assessed. Results: With a gonococcal vaccine of 100% or 50% protective efficacy, gonorrhea prevalence could be reduced by 94% or 62%, respectively, within 2 years if 30% of MSM are vaccinated on presentation for sexually transmitted infection (STI) testing. Elimination of gonorrhea is possible within 8 years with vaccines of ≥ 50% efficacy lasting 2 years, providing a booster vaccination is available every 3 years on average. A vaccine's impact may be reduced if it is not effective at all anatomical sites. Conclusions: Our study indicates that with a vaccine of modest efficacy and an immunization strategy that targets MSM presenting for STI screening, the prevalence of gonorrhea in this population could be rapidly and substantially reduced. Abstract : Modelling was used to assess the potential impact of a Neisseria gonorrhoeae vaccine among MSM. A vaccine of modest efficacy could reduce prevalence substantially, but the impact of vaccination is reduced if the vaccine is ineffective at preventing oropharyngeal infection.